HUBUNGAN ANTARA KECERDASAN INTRAPERSONAL DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 11 KOTA SINGKAWANG - Fazira, Friska Era; Fitriyadi, Slamat; Hendriana, Evinna Cinda (Universitas Islam Sumatera Utara, 2024)
This study aims to: determine the relationship between intrapersonal intelligence and mathematics learning outcomes of class V students at SD Negeri 11 Singkawang City. By using a quantitative approach and correlational research, the aim of this research is to find out how the mathematics learning outcomes of fifth grade students at SD Negeri 11 Singkawang City are related to intrapersonal intelligence. Students in class V at SD Negeri 11 Singkawang City are the subjects of this research. This research involved 20 students as population and sample. Intrapersonal intelligence questionnaires and mathematics learning outcomes tests for class V students were the instruments of this research. Instrument testing consists of validity tests, reliability tests, normality tests, and linearity tests, which are tests of the analytical requirements used. To determine the relationship between intrapersonal intelligence variables and students' mathematics learning outcomes, the data analysis technique used was product moment correlation hypothesis testing and simple linearity regression. The results of the research show that: 1) The intrapersonal intelligence of class V students at SD Negeri 11 Singkawang City is in the high category based on the calculation of the percentage of student scores with an overall average of 69.75. 2) Students' cognitive domain mathematics learning outcomes are in the high category with an overall average of 78.25. 3) There is a relationship between intrapersonal intelligence and the mathematics learning outcomes of class V students at SD Negeri 11 Singkawang City.